PENGGUNAAN STRATEGI INKUIRI DALAM PEMBELAJARAN SEJARAH - Sri Jutmini (PAEDAGOGIA, 2008)
This research is about the study on the effectiveness of inquiry strategy uponstudent's achievement in history subject, dealing with cognitive, affective and creativethinking domains, with student’s entry behaviour, interest in the subject, family backgroundand student's achievement in religion and Pancasila Education as covariates.The inferential analysis such as t-test and anacova were used to test the hypothesis.The result of the testing of the hypothesis revealed that at the level of significance a =0,01, the main hypothesis was accepted. The contribution of student's entry behaviourwas 10,10 %. The study concluded that there was a significant different in student'sachievement using inquiry strategy in the instructional materials and the classicalmethod of teaching. This means that inquiry strategy in the instructional materials wasmore effective than classical learning.